Lifestyle Intervention is Beneficial in Pregnant Women at Risk for Gestational Diabetes - Vinall, Maria (MD Conference Express, 2013)
Lifestyle modifications incorporating healthy diet and increased physical activity in nonpregnant adults are effective for proper weight control as well as prevention of diabetes in at-risk individuals. This article reports on the results of study in pregnant women at risk for gestational diabetes in which a similar lifestyle intervention was effective in improving glucose metabolism and insulin resistance.